Reflections on workload-injury associations in team sport: mistakes, regrets and implications for future research and practice - Hulin, B. (Sport Performance & Science Reports, 2021)
It has been more than 7 years since the acute:chronic workload ratio was first associated with injury risk in cricket fast bowlers. In that time, the commentary and feedback (positive and negative) on the concept of modelling workloads to identify associations with injury has been overwhelming. Naturally, receiving a large amount of criticism over a long period, the value of hindsight and using these methods in practice has helped me appraise my role in this area. Aim The goal of this article is to openly reflect on workload-injury research and acknowledge: i) some areas that could have been conducted better. ii) the limitations and uncertainty that should be considered when attempting to produce practical applications from monitoring workload in team sport.